Sleep disruption among cancer patients following autologous hematopoietic cell transplantation. (March 2018) - Nelson, Ashley; Jim, Heather; Small, Brent; Nishihori, Taiga; Gonzalez, Brian; Cessna, Julie; Hyland, Kelly; Rumble, Meredith; Jacobsen, Paul
Abstract Despite a high prevalence of sleep disruption among hematopoietic cell transplant (HCT) recipients, relatively little research has investigated its relationships with modifiable cognitive or behavioral factors or used actigraphy to characterize sleep disruption in this population. Autologous HCT recipients who were 6–18 months post transplant completed self-report measures of cancer-related distress, fear of cancer recurrence, dysfunctional sleep cognitions, and inhibitory sleep behaviors upon enrollment. Patients then wore an actigraph for 7 days and completed a self-report measure of sleep disruption on day 7 of the study. Among the 84 participants (ageM = 60, 45% female), 41% reported clinically relevant sleep disruption. Examination of actigraph data confirmed that, on average, sleep was disrupted (wake after sleep onsetM = 66 min) and sleep efficiency was less than recommended (sleep efficiencyM = 78%). Cancer-related distress, fear of recurrence, dysfunctional sleep cognitions, and inhibitory sleep behaviors were related to self-reported sleep disruption (p values<0.05) but not objective sleep indices. Results suggest that many HCT recipients experience sleep disruption after transplant. Cancer-related distress, fear of recurrence, dysfunctional sleep cognitions, and maladaptive sleep behaviors are related to self-reported sleep disruption and should be considered targets for cognitive behavioral intervention in this population.